Perception of management personnel in the creation of a learning community - Aguirre Gutiérrez, María Teresa (2022)
The objective of this research was to understand the perception of managers regarding the Good Performance Framework for Managers in the creation of a learning community. A qualitative research, of phenomenological design, was proposed. The sample consisted of 15 directors of public institutions of the primary and secondary level, from a non-probabilistic sampling of an intentional type. The instruments used were: sociodemographic data sheet, semi-structured interview and focus group. The results showed that the management staff knew the management document and made an effort to achieve the assigned competencies as pedagogical leaders. In conclusion, it was possible to understand the managers' perception of the Manager's Good Performance Framework, as the main input to create a learning community in their schools. in public educational institutions, in relation to each of the proposed objectives. The findings made it possible to identify emerging categories that served as support for the interpretation of the results.